NAVIGATING DISRUPTIVE BUSINESS ENVIRONMENTS THROUGH BEHAVIORAL STRATEGY (American Journal of Interdisciplinary Research and Development, 2025)
This paper examines the influence of behavioral strategy in navigating disruptive environments that thrive in volatility, uncertainty, complexities, and ambiguity. Drawing from psychology, organizational behavior and strategic management, behavioral strategy brings to light such dimensions of managerial decision-making as cognitive, emotional and social aside of rationalist presupposition. The research conceptualizes behavioral strategy with respect to some of the lead dimensions such as cognition, biases and heuristics, leadership behavior, group dynamics, and organizational culture with relevance to a disrupted context of technological innovation propelling digitalization, geopolitical instability, sustainability pressures, and global shocks. Of particular interest is the magnification of mental shortcuts when in an uncertainty situation, and the results of such strategic errors. The interaction between managerial cognition, strategic foresight, adaptive learning, and an ambidextrous organization in the platform of resilience building is also a part of the paper. More so, emotional intelligence, humility, and visionary framing leadership behaviors can be cited as important sources of adaptive capacity. The theoretical foundations of the paper include the perspective of bounded rationality, the prospect theory, upper echelons theory and dynamic capabilities, and offer a conceptual framework explaining how behavioral strategy is related to organizational survival and competitive advantage in a disruptive context. It summarizes that organizations that nurture and practice cognitive diversity, psychological safety, and adaptive learning processes stand in a better position to foresee shocks, reduce bias in decision making and attain sustained performance within turbulent environments.